Ethnic politics in the Philippines - Taya, Shamsuddin L. (Cambridge Scholars Publishing, 2010)
A few years ago many analysts and leaders of both the Bangsamoro and the Christian-Filipino peoples wrongly thought they were about to close the chapter of ethniclreligious politics in the Philippines from politics to history, as something of the past, when they all naively thought that the melting pot or integration had started its mission and made remarkable progress towards its goal that is the attainment of a comprehensive, just and lasting political settlement between the Manila government and the Bangsamoro revolutionary groups in the Southern Philippines.Both parties believed that this would lead to the co-existence of religiously/ethnically/tribally divided Philippine society.